Response of the respiratory system to changes in pressure - Alexandrov, J.; Petrov, L. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
In the aquatic environment, there is an increased pressure on the respiratory system of the swimmer. This resistance makes breathing during competition more difficult because of an increase in the requirements of ventilation. The work capacity of the respiratory system during competitive swimming depends on the physical capabilities of this system. The purpose of this study was to fmd a method for estimating the capabilities of the respiratory system for resisting water pressure during breathing.